Adherence to option B+ PMTCT program and its predictors among HIV‐positive women in Ethiopia. A systematic review and meta‐analysis - Habtamu Geremew; Demeke Geremew; Samuel Abdisa; Anteneh Mengist Dessie; Getachew Mullu Kassa; Nurilign Abebe Moges (Health Science Reports, 2023)
Abstract Background Previously, few studies investigated level of adherence to option B+ lifelong antiretroviral therapy (ART) in Ethiopia. However, their findings were inconsistent. Therefore, this review aimed to determine the pooled magnitude of adherence to option B+ lifelong ART and its predictors among human immune virus (HIV)‐positive women in Ethiopia. Methods A comprehensive web‐based search was conducted using PubMed, Cochrane Library, Science Direct, Google scholar, and African Journals Online databases to retrieve relevant articles. STATA 14 statistical software was used to carry out the meta‐analysis. We used the random effects model to account for the large heterogeneity across included studies. Egger's regression test in conjunction with funnel plot and I2 statistics were utilized to assess publication bias and heterogeneity among included studies respectively. Result Twelve studies with a total of 2927 study participants were involved in this analysis. The pooled magnitude of adherence to option B+ lifelong ART was 80.72% (95% confidence interval [CI]: 77.05−84.39; I2 = 85.4%). Disclosure of sero‐status (OR 2.58 [95% CI: 1.55−4.3]), receiving counseling (OR 4.93 [95% CI: 3.21−7.57]), attending primary school and above (OR 2.45 [95% CI: 1.31−4.57]), partner support (OR 2.24 [95% CI: 1.11, 4.52]), good knowledge about prevention of mother‐to‐child transmission (PMTCT) (OR 4.22 [95% CI: 2.02−8.84]), taking less time to reach health facility (OR 1.64 [95% CI: 1.13−2.4]), and good relation with care provider (OR 3.24 [95% CI: 1.96−5.34]) were positively associated with adherence. Whereas, fear of stigma and discrimination (OR 0.12 [95% CI: 0.06−0.22]) and advanced disease stage (OR 0.59 [95% CI: 0.37−0.92]) were negatively associated. Conclusion The level of adherence to option B+ lifelong ART was suboptimal. Strengthened comprehensive counseling and client education on PMTCT, HIV status disclosure, and male partner involvement are important to eliminate mother to child transmission and control the pandemic.